2016
DOI: 10.7860/jcdr/2016/22543.8629
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Induced Lupus Presenting as Oral Mucosal Ulcers with Pancytopenia

Abstract: Drug Induced Lupus Erythematous (DILE) is a rare adverse reaction to a large variety of drugs including Isoniazid (INH), with features resembling idiopathic Systemic Lupus Erythematosus (SLE). Diagnosis require identification of a temporal relationship between drug administered and symptom. It is an idiosyncratic reaction, with no pre-existing lupus. Our case highlights a rare presentation of isoniazid induced lupus with profound pancytopenia and mucosal ulcers, thus posing a diagnostic challenge. The patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…On the other hand, larvae treated with INH after the liver is functional (5-7 dpf) had hepatomegaly without any apparent toxicity in the rest of the larval body. Hepatomegaly is a known clinical manifestation of liver injury induced by INH administration (Nanton et al, 2004;Shah et al, 2016;Wolf & Lavine, 2000). To our knowledge, this is the first study demonstrating INH induced hepatomegaly in the zebrafish model.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, larvae treated with INH after the liver is functional (5-7 dpf) had hepatomegaly without any apparent toxicity in the rest of the larval body. Hepatomegaly is a known clinical manifestation of liver injury induced by INH administration (Nanton et al, 2004;Shah et al, 2016;Wolf & Lavine, 2000). To our knowledge, this is the first study demonstrating INH induced hepatomegaly in the zebrafish model.…”
Section: Discussionmentioning
confidence: 80%
“…Dysregulation of the liver immune environment is thought to play a critical role in the initiation and progression of DILI ( Segovia-Zafra et al, 2021 ). One previous study had shown that lupus erythematosus developed in patients with INH-ILI ( Shah et al, 2016 ). Lupus erythematosus is a well-known disease of the immune system, thus INH-ILI may be also related to the immune response.…”
Section: The Molecular Mechanism Involved In Isoniazid-induced Liver ...mentioning
confidence: 99%
“…[8][9][10] Efek yang ditimbulkan ADR dapat berupa eritema sampai efek samping berat yang mengancam jiwa seperti Stevens Johnson Sindrome (SJS) 11 dan ADR juga dapat memicu terjadinya sistemik lupus eritematous (SLE) pada penderitanya. [12][13][14][15] SJS merupakan reaksi mukokutan akut, ditandai oleh nekrosis epidermis luas dengan keterlibatan minimal 2 membran mukosa yang dipicu oleh obat, jarang karena infeksi dan keganasan. 16 SLE adalah suatu kondisi inflamasi yang berhubungan dengan gangguan autoimun, sistem tubuh menyerang jaringannya sendiri yang menyebabkan kerusakan multiorgan ditandai dengan 4 dari 11 kriteria seperti ruam malar, ruam diskoid, fotosensitifitas, ulser pada rongga mulut, artritis, serositis, gangguan renal, gangguan neurologi, gangguan hematologi, gangguan imunologis, antibodi antinuclear (ANA).…”
Section: Pendahuluanunclassified